Circ-CDK8 regulates SLC7A11-mediated ferroptosis by inhibiting miR-615-5p to promote progression in oral squamous cell carcinomas - Sun, Kai; Gao, Ling; Li, Shaoming; Zheng, Jingjing; Zhu, Zhuang; Zhi, Keqian; Ren, Wenhao (Frontiers in Pharmacology, 2024)
Introduction: Ferroptosis is a new mode of programmed cell death distinct from necrosis, apoptosis, and autophagy, induced by iron-ion-dependent lipid peroxide accumulation. Circular RNAs are a class of endogenous non-coding RNAs that regulate the biological behavior of tumors. However, the role of circ-CDK8 in regulating ferroptosis, migration, and invasion of oral squamous cell carcinoma (OSCC) remains unknown. Methods: The effect of circ-CDK8 on OSCC cell ferroptosis, migration, and invasion was evaluated using CCK-8, wound healing, transwell, reactive oxygen species (ROS), malondialdehyde (MDA), and GSH assays and Western blotting. Bioinformatics analyses and luciferase reporter assays were performed and revealed targeted relationships between circ-CDK8 and miR-615-5p, miR-615-5p and SLC7A11. Interference with circ-CDK8 expression reduced SLC7A11 expression by sponging miR-615-5p, suppressed OSCC cell migration and invasion, and promoted ferroptosis by increasing ROS, MDA, and iron levels and decreasing GSH and GPX4 levels in OSCC cells. Furthermore, in vivo, animal experiments confirmed that circ-CDK8 interference inhibited OSCC cell proliferation and SLC7A11 expression. Results: Collectively, this study revealed a novel strategy to upregulate erastin-induced ferroptosis in OSCC cells via the circ-CDK8/miR-615-5p/SLC7A11 axis, providing new insights into OSCC and a potential therapeutic strategy for OSCC.